Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s00366-022-01626-5
|View full text |Cite
|
Sign up to set email alerts
|

Finite volume simulations of particle-laden viscoelastic fluid flows: application to hydraulic fracture processes

Abstract: Accurately resolving the coupled momentum transfer between the liquid and solid phases of complex fluids is a fundamental problem in multiphase transport processes, such as hydraulic fracture operations. Specifically we need to characterize the dependence of the normalized average fluid-particle force F on the volume fraction of the dispersed solid phase and on the rheology of the complex fluid matrix, parameterized through the Weissenberg number W i measuring the relative magnitude of elastic to viscous stres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…A coupled CFD-DEM approach was used for modeling particle-laden flows [13]. The so-called unresolved approach [13,39,40] was employed in this study because only the bulk behavior of the suspension is of interest. In this formulation, the particle size is smaller than the computational grid size.…”
Section: Particle-laden Flowsmentioning
confidence: 99%
“…A coupled CFD-DEM approach was used for modeling particle-laden flows [13]. The so-called unresolved approach [13,39,40] was employed in this study because only the bulk behavior of the suspension is of interest. In this formulation, the particle size is smaller than the computational grid size.…”
Section: Particle-laden Flowsmentioning
confidence: 99%
“…The governing equations for the transient, incompressible, and isothermal flow of wormlike micellar solutions include the continuity equation, the momentum equation, and the constitutive equations that define the extra elastic stress contribution, as reported by previous research [ 7 , 22 , 30 , 33 , 37 ].…”
Section: Mathematical Model and Numerical Considerationsmentioning
confidence: 99%
“…Su et al [ 32 ] investigated a sphere’s settling in Giesekus and FENE-P fluids and found that shear thinning weakens the oscillation of the settling velocity of the sphere compared with that in the Oldroyd-B fluids under identical rheological parameters. Fernandes et al [ 33 ] developed a fluid–particle interaction force model through a direct simulation method by considering the volume fraction of the dispersed solid phase in Oldroyd-B fluids, which is applicable to the dense particle-laden flows in viscoelastic fluids. Qin et al [ 34 ] recently developed a fully resolved simulation method based on the immersed boundary–lattice Boltzmann method using the Oldroyd-B and the Giesekus constitutive equations to investigate the particle dynamics in viscoelastic fluids, which shows good prospects for the simulation of flow behaviors of the particle-laden viscoelastic fluids.…”
Section: Introductionmentioning
confidence: 99%
“…A typical example of a structured fluid is a micellar solution, which consists of a dispersion of micelles in a solvent. When surfactant molecules (which have a hydrophilic group (water-loving) that is chemically bonded to a hydrophobic group (water-hating)) are in the solution, they will self-assemble into aggregates such as spherical and wormlike micelles, bilayers, among others [7][8][9]. The rheological behaviour of micelles makes them highly attractive in the industry, specially in oil-recovery processes and in drilling operations [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%